Comparison of the hydrogen powered homogeneous charge compression ignition mode with multiple injection schedules and the dual fuel mode using a twin-cylinder engine. (1st January 2021) - Sathishkumar, S.; Ibrahim, M. Mohamed
Abstract: The present work discusses the influence of injection schedules in hydrogen diesel homogeneous charge compression ignition (HDHCCI) mode, the experiments were carried out in three distinct diesel injection schedules like single pulse, double pulse and multi-pulse at low load operation. The maximum reachable hydrogen energy shares (HES) are 27.46%, 26.97% and 39.96% for a single pulse, double pulse and multi-pulse respectively. For almost all HES levels, the single pulse and double pulse HDHCCI mode provided ultra-low NO emission when compared with hydrogen diesel dual fuel (HDDF) mode. The multi-pulse injection increased the brake thermal efficiency (BTE) compared with single pulse and double pulse injection, since the timing of injection pulse 3 (IP3) in multi-pulse significantly altered the combustion characteristics of HDHCCI mode. Locating the IP3 in the window of 30–40 °BTDC (before cool flame) enhanced the BTE and reduced the brake specific energy consumption (BSEC) of the engine. Graphical abstract: Image 1 Highlights: Injection schedule influence the hydrogen diesel HCCI (HDHCCI) mode. Single pulse HDHCCI mode provides ultra-low NO emission for entire HES levels. No significant change in performance of HDHCCI with double pulse injection. Multi-pulse HDHCCI mode recovers the combustion and increases the HES level. Multi-pulse enhances the performance of HDHCCI mode and reach near to HDDF mode.